2022
DOI: 10.2131/jts.47.389
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of differential metabolites in serum and urine of bamaxiang pigs bitten by <i>trimeresurus stejnegeri</i> based on UPLC-Q-TOF/MS metabolomics technology

Abstract: Trimeresurus stejnegeri is one of the top ten venomous snakes in China, and its bite causes acute and severe diseases. Elucidating the metabolic changes of the body caused by Trimeresurus stejnegeri bite will be beneficial to the diagnosis and treatment of snakebite. Thus, an animal pig model of Trimeresurus stejnegeri bite was established, and then the metabolites of serum and urine were subsequently screened and identified in both ESI+ and ESI-modes identified by ultra-performance liquid chromatography-quadr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The key metabolites identified in the Trimeresurus stejnegeri bite were deoxycholic acid, lithocholic acid, tryptophan and hypoxanthine, and the key metabolic pathways were Liver disease due to cystic fibrosis, Hyperbaric oxygen exposure, Biliary cirrhosis and Tryptophanuria. Compared with thekey metabolites in Naja atra bites, hypoxanthine, arginine and tryptophan were common metabolites and showed the same trend, suggesting some similarities between our Naja atra bites and the bites of Trimeresurus stejnegeri [ 17 , 18 ]. The changes in these metabolites suggest that the changes in metabolites of Naja atra bite, Bungarus multicinctus bite and Trimeresurus stejnegeri bite pigs are related to the composition of snake venom, and also lay the foundation for the next exploration of the effects of specific components of snake venom on the metabolites and metabolic pathways of the body.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The key metabolites identified in the Trimeresurus stejnegeri bite were deoxycholic acid, lithocholic acid, tryptophan and hypoxanthine, and the key metabolic pathways were Liver disease due to cystic fibrosis, Hyperbaric oxygen exposure, Biliary cirrhosis and Tryptophanuria. Compared with thekey metabolites in Naja atra bites, hypoxanthine, arginine and tryptophan were common metabolites and showed the same trend, suggesting some similarities between our Naja atra bites and the bites of Trimeresurus stejnegeri [ 17 , 18 ]. The changes in these metabolites suggest that the changes in metabolites of Naja atra bite, Bungarus multicinctus bite and Trimeresurus stejnegeri bite pigs are related to the composition of snake venom, and also lay the foundation for the next exploration of the effects of specific components of snake venom on the metabolites and metabolic pathways of the body.…”
Section: Discussionmentioning
confidence: 82%
“…This is one of the most important means of finding potential biomarkers. We previously reported that we have used Bama miniature pigs as an animal model, to explore the changes of metabolites and analyze the potential biomarkers and metabolic pathways after the Bungarus multicinctus bite and Trimeresurus stejnegeri bite [ 17 , 18 ]. In the present study, we still used an animal model of Naja atra bite in Bama miniature pigs to screen, identify and validate the differential metabolites using untargeted and targeted metabolomics techniques.…”
Section: Introductionmentioning
confidence: 99%